2015
DOI: 10.1371/journal.ppat.1004655
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Systemic Tetrahydrobiopterin Bioavailability and Increased Oxidized Biopterins in Pediatric Falciparum Malaria: Association with Disease Severity

Abstract: Decreased bioavailability of nitric oxide (NO) is a major contributor to the pathophysiology of severe falciparum malaria. Tetrahydrobiopterin (BH4) is an enzyme cofactor required for NO synthesis from L-arginine. We hypothesized that systemic levels of BH4 would be decreased in children with cerebral malaria, contributing to low NO bioavailability. In an observational study in Tanzania, we measured urine levels of biopterin in its various redox states (fully reduced [BH4] and the oxidized metabolites, dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 67 publications
2
36
2
Order By: Relevance
“…In ten out of eleven studies comparing healthy controls with either uncomplicated [25, 32, 34, 35, 37, 4345], severe [34, 35, 43, 45, 46] or cerebral falciparum malaria [25, 32, 37, 44, 45] or uncomplicated [43, 47] or severe [43] vivax malaria, a similar pattern in changes was observed for Ang-1 and Ang-2 levels: a decrease of Ang-1 [25, 32], an increase of Ang-2 [25, 32, 34, 35, 37, 4347] and consequently an increase of the Ang-2/Ang-1 ratio [25, 32] (see Additional files 3, 4, 5). Adults and children, living either in endemic areas or travellers in non-endemic areas all showed these similar changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ten out of eleven studies comparing healthy controls with either uncomplicated [25, 32, 34, 35, 37, 4345], severe [34, 35, 43, 45, 46] or cerebral falciparum malaria [25, 32, 37, 44, 45] or uncomplicated [43, 47] or severe [43] vivax malaria, a similar pattern in changes was observed for Ang-1 and Ang-2 levels: a decrease of Ang-1 [25, 32], an increase of Ang-2 [25, 32, 34, 35, 37, 4347] and consequently an increase of the Ang-2/Ang-1 ratio [25, 32] (see Additional files 3, 4, 5). Adults and children, living either in endemic areas or travellers in non-endemic areas all showed these similar changes.…”
Section: Resultsmentioning
confidence: 99%
“…NO inhibits the exocytosis of Weibel–Palade bodies [59], organelles in endothelial cells that store both vWF and Ang-2. NO levels and cofactors required for NO synthesis are known to be reduced during P. falciparum infection [34, 35, 44] and higher NO levels are associated with lower Ang-2 levels [34], whereas NO inhibitors positively correlate with Ang-2 [45]. Several processes contributing to the decreased NO levels during malaria have been studied, such as substrate limitation and increase in NO inhibitors [35], but these are beyond the scope of this review.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of brain tissue from P. berghei ANKA-infected mice have shown evidence of direct inactivation of the NOS enzyme complex, including decreased eNOS phosphorylation and proportional increases in eNOS and nNOS monomers [40]. NO synthesis could also be impaired by insufficient availability of the essential NOS cofactor tetrahydrobiopterin [41,42]. In addition, relative accumulation of the endogenous NOS inhibitor asymmetric dimethylarginine has been observed in both children [5,43] and adults [44] with severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Urinary BH4 is low in both pediatric 3 and adult 4 severe malaria. Severe malaria is characterized by hyperphenylalaninemia, 57 impaired vasodilation, 8 and low plasma and urinary nitrite and nitrate concentrations.…”
mentioning
confidence: 98%
“…22–26 The major BH4 oxidation product 7,8-BH2 is catalytically inactive and can compete with BH4 for binding to NOS, thereby promoting NOS uncoupling. 25,26 In both pediatric and adult patients with severe malaria, urinary 7,8-BH2 was found to be increased, 3,4 suggesting that oxidation could contribute to BH4 depletion and that 7,8-BH2 accumulation could contribute to NOS uncoupling. A recent intravital microscopy study demonstrated impaired vasodilation of pial vessels in P. berghei ANKA-infected mice following acetylcholine or NMDA stimulation.…”
mentioning
confidence: 99%